2014
DOI: 10.4238/2014.february.13.12
|View full text |Cite
|
Sign up to set email alerts
|

Acute heat stress and dietary methionine effects on IGF-I, GHR, and UCP mRNA expression in liver and muscle of quails

Abstract: ABSTRACT. This study evaluated the expression of insulin-like growth factor I (IGF-I), growth hormone receptor (GHR), and uncoupling protein (UCP) mRNA in muscle and liver of quails that were in thermal comfort or exposed to heat stress and that were fed diets with or without methionine supplementation. Meat quails were fed a diet that either met the nutritional demands for methionine (MS) or did not meet this demand (methioninedeficient diet, MD). The animals were either kept at a thermal comfort temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…This means, the body temperature is not constant but varies with water temperature which may have direct effects on metabolic and endocrine parameters in contrast to endothermic mammals. Contrary to the results of the fish study ( 32 ), IGF-II level variation was not inversely proportional to that in ambient temperature in the present study, probably due to the potential negative effect of heat stress on the expression of growth-related genes ( 37 ). It has been also suggested that potential environmental effects on IGF-system in market pigs are strongly dependent on the farm management system.…”
Section: Discussioncontrasting
confidence: 99%
“…This means, the body temperature is not constant but varies with water temperature which may have direct effects on metabolic and endocrine parameters in contrast to endothermic mammals. Contrary to the results of the fish study ( 32 ), IGF-II level variation was not inversely proportional to that in ambient temperature in the present study, probably due to the potential negative effect of heat stress on the expression of growth-related genes ( 37 ). It has been also suggested that potential environmental effects on IGF-system in market pigs are strongly dependent on the farm management system.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, when the cell or organism succumbed to a non‐fatal stress response, HSP70 over‐expression may protect them from injury. In addition, it is reported that heat stress negatively affected the expression of growth‐related genes and that Met supplementation was necessary to appropriately maintain the levels of insulin‐like growth factor I (IGF‐I) and growth hormone receptor (Del Vesco, Gasparino, Zancanela, Grieser, Guimaraes et al., ). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic IGF‐I synthesis depends on the action of growth hormone (GH) in the liver through binding to the GH receptor (Guzmán et al., ). In broilers, methionine supplementation increases the mRNA expression of the GH receptor in the liver (Del Vesco et al., ), whereas in quail livers, the GH receptor mRNA expression is greater in animals that are supplemented with methionine than in animals that have methionine restriction (Del Vesco et al., ). Therefore, methionine likely increases the synthesis of the GH receptor in the liver, which then promotes IGF‐I synthesis and increases the level of this growth factor in the blood.…”
Section: Discussionmentioning
confidence: 99%